PTH-065 The impact of changes to the nice guideline on the use of biologic agents in ulcerative colitis in a uk district general hospital. (22nd June 2015) - Koshy, R Mary; Steed, H; Nordon, R; Brookes, MJ
Abstract : Introduction: After pressure from patient and clinical groups NICE have reversed their position on biologics 1, 2 in subacute ulcerative colitis (UC) and it will be available to patients in 2015. Method: A retrospective review of the use of infliximab for the treatment of UC in a single centre DGH between 2011 and 2014. Results: Ten patients received infliximab for acute severe UC and ten for subacute UC. In the 12 months pre-infliximab these patients received 40 courses of prednisolone between them (Table 1 ). All subacute patients had received immunomodulators. All subacute patients had a partial or complete clinical (MAYO score) and biochemical response following infliximab induction, compared to 50% of the acute severe group. Two patients remain on long-term infliximab and in remission. Colectomy was required within 12 months for 55.6% of patients with acute severe disease and 44.4% of those with subacute activity. 60% of the remaining subacute patients (n = 3) have received steroids since infliximab. Conclusion: NICE change of position 2 echos current practice in our centre and with the change in guidelines we may hope to see a reduction in steroid use prior to the use of biological treatment. However the long term success of infliximab in UC is limited. Subacute patients showed better immediate outcomes in terms of biochemical and clinical response, but at 12 months, outcomes were similar in both groups. Work is needed to identify the likely responders to make its use cost effective and evidence based guidance is needed on the clinical benefits of switching to alternative biological agents if infliximab fails. Disclosure of interest: None Declared. References: Infliximab for acute exacerbations of ulcerative colitis. Available at: https://www.nice.org.uk/guidance/ta163 . Accessed on 07/01/2015 Ulcerative colitis (moderate, severe) – infliximab (review TA140), adalimumab (review TA262) & golimumab (2nd line) [ID695]. Available at: http://www.nice.org.uk/Guidance/InDevelopment/GID-TAG357 . Accessed on 23/02/2015